Light induced transthylakoidal proton gradient is a key signal driving the downward migration of motile diatoms in sediments - Jérôme Morelle; Johann Lavaud; Douglas A. Campbell; Silja Frankenbach; João Serôdio (Scientific Reports, 2025)
Abstract Pennate diatoms are photosynthetic microorganisms capable of directed motility in response to light. In sedimentary habitats, many epipelic pennate diatoms exhibit photophobic migration under high light, a behaviour critical for avoiding photodamage and key to ecological success. While the ecophysiological significance of this behaviour is well-documented, the mechanisms linking light sensing to motility remain poorly understood. This study investigated whether the transthylakoidal proton gradient (ΔpH), generated under high light, intervenes in the signal transduction mechanism driving photophobic migration. The impact of the ΔpH inhibitors Nigericin and Carbonyl cyanide 4-(trifluoromethoxy)phenylhydrazone (FCCP) on the vertical migration of benthic pennate diatoms was monitored using non-destructive imaging chlorophyll fluorometry on intertidal diatom-dominated microphytobenthos biofilms. The results showed that ΔpH inhibition significantly reduced the downward, high light-avoiding, migratory response, supporting the hypothesis that ΔpH plays a central role in mediating this response. Additionally, results showed that the effective quantum yield of PSII and non-photochemical quenching (NPQ) were impacted by ΔpH inhibition with a dose-dependent effect. These findings strongly support ΔpH as an integrative signal linking physiological and behavioural photoprotection mechanisms and suggest that ΔpH may also modulate intracellular signalling, explaining the efficient capacity of pennate diatoms to cope with high light exposure in benthic habitats.